The Effect of Leadership, Work Discipline, Work Motivation, Occupational Health and Safety (K3) on Employee Productivity - Aditiya Dwi Raharja; Bambang Mursito; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of leadership, work discipline, work motivation, and occupational health and safety (OHS) on employee productivity at the Solo Balapan Locomotive Depot. The focus of this study is to determine the extent to which each of these variables contributes to improving the productivity of operational employees. This research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to 66 operational employees as respondents and analyzed using multiple linear regression analysis to examine the effect of independent variables on employee productivity. The results indicate that leadership, work discipline, work motivation, and occupational health and safety (OHS) each have a significant effect on employee productivity. Simultaneously, all independent variables in the regression model are considered feasible and capable of explaining variations in employee productivity, indicating that integrated management of leadership, discipline, motivation, and OHS implementation plays an important role in enhancing employee productivity.